A new tool GSEQ-FRC for two-dimensional field-reversed configuration equilibrium. (24th June 2021) - Ma, H.J.; Xie, H.S.; Deng, B.H.; Bai, Y.K.; Cheng, S.K.; Li, Y.; Chen, B.; Tuszewski, M.; Zhao, H.Y.; Liu, J.Y.
Abstract: A new tool (GSEQ-FRC) is developed for solving two-dimensional equilibrium of the field-reversed configuration (FRC) based on fixed boundary and free boundary conditions that includes external coils. Benefiting from the two-parameter modified rigid rotor radial equilibrium model and the numerical approaches presented (Ma et al 2021 Nucl. Fusion 61 036046) in this work, the GSEQ-FRC code is used to study the equilibrium properties of FRC quantitatively and will be used for fast FRC equilibrium reconstruction. In GSEQ-FRC, the FRC equilibrium is determined by two parameters, i.e. the ratio between thermal pressure and magnetic pressure at the separatrix β s, and the normalized scrape of layer width δ s . Examples with fixed and free boundary conditions are given to demonstrate the capability of GSEQ-FRC for equilibrium calculations. This new tool is used to quantitatively study the factors affecting the shape of the FRC separatrix, which reveals how the FRC changes from racetrack-like to ellipse-like.